2018
DOI: 10.1111/exd.13454
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2/STAT3 pathway is involved in the anti‐melanoma effects of atractylenolide I

Abstract: In this study, we aimed to investigate the anti-melanoma effects and the JAK2/STAT3 pathway-related mechanism of action of atractylenolide I in human melanoma cells. Our results showed that atractylenolide I effectively reduced viability, induced apoptosis and inhibited migration of melanoma cells. Meanwhile, atractylenolide I decreased the protein expression levels of phospho-JAK2 and phospho-STAT3, and in turn downregulated the mRNA levels of STAT3-targeted genes, including Bcl-xL, MMP-2 and MMP-9. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…JAK2 is a well-known upstream regulator of STAT3 activation in cancer cells (Bowman et al, 2000), and the JAK2/STAT3 pathway has been shown to alter the expression of key oncogenes and tumor suppressor genes to enhance the growth, survival, and metastasis of CRC cells (Xiong et al, 2008). Previous studies have reported that AT-I can inhibit JAK2 activation, indicating that the AT-I-induced downregulation of STAT3 phosphorylation is associated with changes in JAK2 (Fu et al, 2018). Consistent with these findings, we also found that AT-I can markedly reduce JAK2 phosphorylation in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…JAK2 is a well-known upstream regulator of STAT3 activation in cancer cells (Bowman et al, 2000), and the JAK2/STAT3 pathway has been shown to alter the expression of key oncogenes and tumor suppressor genes to enhance the growth, survival, and metastasis of CRC cells (Xiong et al, 2008). Previous studies have reported that AT-I can inhibit JAK2 activation, indicating that the AT-I-induced downregulation of STAT3 phosphorylation is associated with changes in JAK2 (Fu et al, 2018). Consistent with these findings, we also found that AT-I can markedly reduce JAK2 phosphorylation in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…AT-I is a novel TLR4-antagonizing agent [20], and it exerted anti-tumor effects on colorectal cancer, bladder cancer and melanoma [17][18][19], then we investigated whether it could suppress tumorigenesis in breast cancer via inhibiting TLR4/NF-κB pathway. Firstly, we found that AT-I could inhibit cell growth, proliferation, migration and invasion, and induce apoptosis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizoma Atractylodis Macrocephalae, one of the traditional Chinese crude materials, had signi cant gastrointestinal tract protective, neuroprotective and immunomodulatory activities [13], and numerous lines of evidence showed that it also exerted anti-tumor, anti-in ammatory and antioxidant effects [13,14]. Atractylenolide I (AT-I), the major bioactive component from Rhizoma Atractylodes Macrocephalae, also had multiple therapeutic activities including anti-in ammatory [15,16] and anti-tumor effects [17][18][19]. Speci cally, AT-I could ameliorate LPS-induced lung damages in mouse model [15], and suppressed LPS-induced NO release and diminished pro-in ammatory cytokines levels in BV-2 cells [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ursolic acid in GRR had a strong effect on inducing apoptosis through JAK2/STAT3 in colorectal cancer cells [36]. Atractylenolide I could induce apoptosis in bladder cancer cells by apoptotic pathway, cell cycle progression and PI3K/Akt/mTOR signaling pathway [37], and reduce viability, induced apoptosis and inhibited migration of melanoma cells [17]. Indirubin in IN inhibited JAK/STAT3 to promote apoptosis in human pancreatic cancer cells [38].…”
Section: Molecular Dockingmentioning
confidence: 99%